(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Article the purpose and content of the promotion of the non-stop and professionalism of the Intern, The Pedagogy of the norm of training of personnel is focused on the side of the intern’s learning and competence. Also, "the profession has continued the activity of a cliff" competencies to replace with "the profession is capable of increasing AK", this baklaj bakkituving pedagogical activity is able to get a place in the process of knowing the tolerance of labor education (self) and professional standard characteristic requires a certain analysis.